Congenital choledochal malformations in children: management strategies - Rawat, Jiledar; Singh, Sudhir; Chaubey, Digamber (International Surgery Journal, 2017)
Background: A Congenital Choledochal Malformations (CCM) is common congenital defect of biliary tree in Asian subcontinent. Presentations of CCM are vague from asymptomatic to life threatening cholangitis or pancreatitis. Complete cyst excision and bilioenteric anastomosis is now accepted surgical treatment. Methods: This is a retrospective study of five years duration. In this study the clinical presentation, haematological, biochemical and radiological findings, operative procedure and outcome were studied from case records. Results: Total of 20 patients were studied, with clinical presentation of recurrent abdominal pain in eight cases, previous history of cholangitis in five cases, acute cholangitis two cases, biliary peritonitis in four cases and previous history of pancreatitis in one case. In 13 cases Roux-en-Y hepaticojejunostomy (RYHJ) and in 4 cases hepaticoduodenostomy (HD) done after cyst excision. One case of type II CCM managed with only cyst excision, in two cases Lilly’s procedure, one case requires temporary external drainage and in two cases temporary internal drainage done in view on cholangitis and jaundice. Conclusions: However, the definitive treatment of CCM is complete cyst excision and bilioenteric anastomosis, though lot of other temporary majors are also required at different stages of disease.